Quantifying Cell‐Derived Changes in Collagen Synthesis, Alignment, and Mechanics in a 3D Connective Tissue Model. Issue 10 (1st February 2022) - Wilks, Benjamin T.; Evans, Elisabeth B.; Howes, Andrew; Hopkins, Caitlin M.; Nakhla, Morcos N.; Williams, Geoffrey; Morgan, Jeffrey R.
Abstract: Dysregulation of extracellular matrix (ECM) synthesis, organization, and mechanics are hallmark features of diseases like fibrosis and cancer. However, most in vitro models fail to recapitulate the three‐dimensional (3D) multi‐scale hierarchical architecture of collagen‐rich tissues and as a result, are unable to mirror native or disease phenotypes. Herein, using primary human fibroblasts seeded into custom fabricated 3D non‐adhesive agarose molds, a novel strategy is proposed to direct the morphogenesis of engineered 3D ring‐shaped tissue constructs with tensile and histological properties that recapitulate key features of fibrous connective tissue. To characterize the shift from monodispersed cells to a highly‐aligned, collagen‐rich matrix, a multi‐modal approach integrating histology, multiphoton second‐harmonic generation, and electron microscopy is employed. Structural changes in collagen synthesis and alignment are then mapped to functional differences in tissue mechanics and total collagen content. Due to the absence of an exogenously added scaffolding material, this model enables the direct quantification of cell‐derived changes in 3D matrix synthesis, alignment, and mechanics in response to the addition or removal of relevant biomolecular perturbations. To illustrate this, the effects of nutrient composition, fetal bovine serum, rho‐kinase inhibitor, and pro‐ and anti‐fibrotic compounds on ECM synthesis, 3D collagen architecture, and mechanophenotype are quantified. Abstract : A three‐dimensional (3D) scaffold‐free human connective tissue model is presented that facilitates the de novo synthesis of a highly‐aligned, collagen‐rich extracellular matrix (ECM). This model enables the direct quantification of cell‐derived changes in 3D ECM synthesis, alignment, and mechanics in response to biomolecular perturbations and may be useful for better understanding complex diseases of the ECM like fibrosis.